The DAGAABA ENCOUNTER WITH THE CHRISTIAN FAITH: MISSIOLOGICAL IMPLICATIONS FOR THE CHURCH IN THE DAGAABA LAND - Diboro, Paul Kang-Ewala Diboro (Ghana journal of religion and theology, 2018)
The study reviews how Christianity spread in Northern Ghana, in the early stages of its expansion, particularly among the Dagaaba, through the Catholic Missionaries (White Fathers). It draws attention to important missionary strategies that were employed, crucial missiological issues that emerged and the implications for the contemporary churches in Ghana. The study employed the historical approach in analysing the data on indigenous missions among the Dagaaba. It reveals that in the conversion of the Dagaaba to the Christian faith, the following strategies were essential: use of Dagaare; socialization; collaboration with indigenous people (catechists), the provision of social services and respect for the traditional worldview